2020
DOI: 10.21273/hortsci15320-20
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Silicon Nutrition to Hydroponically Grown Sweet Basil

Abstract: Sweet basil (Ocimum basilicum L.) is a globally cultivated and consumed herb known for its unique aroma and flavor. Sweet basil grows best in warm temperatures, and productivity and marketability decrease when grown under cool conditions (<10 °C). Silicon (Si) is not considered an essential plant nutrient, but it can be beneficial to Si macroaccumulator plants by alleviating several biotic and abiotic stresses. Recent studies have shown that some microaccumulator species may also benefit from Si. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Hoffmann et al [181] observed that cucumber is a Si accumulator species, whereas tomato is a non-accumulator. Li [182] also declared that lettuce, bok choy, and basil are Si non-accumulators.…”
Section: Silicon (Si)mentioning
confidence: 99%
“…Hoffmann et al [181] observed that cucumber is a Si accumulator species, whereas tomato is a non-accumulator. Li [182] also declared that lettuce, bok choy, and basil are Si non-accumulators.…”
Section: Silicon (Si)mentioning
confidence: 99%
“…Increase leaf resiliency, plant fresh mass, plant dry matter content, visual quality, and levels of soluble sugars, starch and nonenzymatic antioxidants, but does not improve chilling injury symptoms (Larsen et al, 2020;Larsen et al, 2022b;Larsen et al, 2023) Artificial lighting Supplement with UV-B light at 0.5 kg•s−3 for 4 days and then white light for 1 day prior to harvest Preharvest 10°C Maintain higher levels of phenolic acids and antioxidant activity (Dos et al, 2020) Drought stress Irrigate at 100% field capacity Preharvest 12°C Maintain higher levels of volatile oils (Jordan et al, 2017) Plant nutrition Supplement nutrient solution with 4 mg•L −1 Se Preharvest 8°C Reduce ethylene production and increase antioxidants, total phenols and rosmarinic acid (Puccinelli et al, 2020) Plant nutrition Supplement nutrient solution with silicon 75 ppm Si Preharvest Unspecified Increase plant height and weight, potentially increase frost tolerance (Li et al, 2020) Time of harvest Harvest basil in the afternoon or evening NA 12°C…”
Section: Preharvest 4°c and 12°cmentioning
confidence: 99%
“…Silicon amendments may also benefit basil postharvest by alleviating cold stress. Silicon (Si; 75 ppm) incorporated into the nutrient solution of a hydroponic growing system significantly increased basil shoot height and weight without negatively affecting plant morphology and led to higher survival rates with reduced cold injury after an unintentional frost event (Li et al, 2020). How nutrient applications during production affect volatile composition and browning of basil leaves needs to be further studied to understand ideal recommendations for optimizing postharvest quality.…”
Section: Plant Nutritionmentioning
confidence: 99%
“…Technologies proven to be effective in conventional cultivation are now being explored in hydroponics, such as inoculation with bacteria that promote plant growth, which can result in mass gains in lettuce (Moreira et al, 2022) and basil (Kolega et al, 2020), application of beneficial elements such as Si, which also resulted in an increase in fresh mass in basil plants (Li et al, 2020), and different types of biostimulants, capable of promoting plant growth and quality (Parađiković et al, 2019). However, there is a range of compounds that need studies aiming at their application in hydroponic systems, including vitamins.…”
Section: Introductionmentioning
confidence: 99%